Swedish and Norwegian Police Interviewers' Goals, Tactics, and Emotions When Interviewing Suspects of Child Sexual Abuse - Magnusson, Mikaela; Joleby, Malin; Luke, Timothy J.; Ask, Karl; Lefsaker Sakrisvold, Marthe (Frontiers in Psychology, 2021)
As the suspect interview is one of the key elements of a police investigation, it has received a great deal of merited attention from the scientific community. However, suspect interviews in child sexual abuse investigations is an understudied research area. In the present mixed-methods study, we examine Swedish (n = 126) and Norwegian (n = 52) police interviewers’ self-reported goals, tactics, and emotional experiences conducting interviews with suspected child sexual abuse offenders. Following a qualitative approach, we asked the practitioners how they manage different emotions that may arise during the interview. The thematic analysis revealed extreme consistency regarding the importance of not expressing emotions in the interview room. Instead, participants described different strategies that could be used after the interview to manage and process their emotional reactions. The quantitative analyses, on the other hand, found associations between the interviewers’ self-reported goals, tactics, and emotions during suspect interviews. Specifically, interviewers who reported experiencing more negative emotions were more likely to employ confrontational tactics. Cross-country differences were observed regarding the interviewers’ self-reported tactics and goals, with Swedish interviewers using confrontational tactics and prioritizing obtaining a confession from the suspect more frequently compared to Norwegian interviewers. Organizational differences between countries may explain these findings. While almost two decades have passed since Norway implemented a research-based interview model (KREATIV), Sweden is still working towards creating and implementing a national model. The present findings provide an initial exploration of the potentially complex relationship between the goals, tactics, and emotional experiences of police interviewers who question child sexual abuse suspects.